Assessing the genetic diversity of cowpea [Vigna unguiculata (L.) Walp.] germplasm collections using phenotypic traits and SNP markers - Nelia Nkhoma; Hussein Shimelis; Mark D. Laing; Admire Shayanowako; Isack Mathew (BMC Genetics, 2020)
Abstract Background Productivity of cowpea [Vigna unguiculata (L.) Walp] in sub-Sahara Africa is curtailed by a lack of farmer-preferred and improved cultivars and modern production technologies. The objectives of the study were to determine the extent of genetic diversity present among a collection of cowpea accessions from Zambia and Malawi using phenotypic traits and single nucleotide polymorphism (SNP) markers and, to select distinct and complementary parental lines for cultivar development. One hundred cowpea genotypes were evaluated for agronomic traits in two selected sites in Zambia, using a 10 × 10 alpha lattice design with two replications. Ninety-four of the test genotypes were profiled with 14,116 SNP markers. Results Number of pods plant− 1 (NPP), pod length (PDL), and number of seeds pod− 1 (NSP), were significantly (p < 0.05) affected by genotype × environment interaction effects. Genotypes such as CP411, CP421, CP645, CP732, Chimponongo, and MS1–8–1-4 exhibited higher grain yield of > 1200 kg/ha with excellent performance in yield components such as NSP, PDL, HSW and GYD. Grain yield had significant (p < 0.05) associations with NPP (r = 0.50), NSP (r = 0.46) and PDL (r = 0.42) useful for simultaneous selection for yield improvement in cowpea. The SNP markers revealed gene diversity and polymorphic information content of 0.22 and 0.17, respectively, showing that the tested cowpea accessions were genetically diverse. Test genotypes were classified into four genetic groups irrespective of source of collection allowing selection and subsequent crosses to develop breeding populations for cultivar development. Conclusions Genotypes Bubebe, CP411, CP421, CP645, Chimponogo and MS1–8–1-4 were identified to be the most genetically divergent and high yielding making them ideal parental lines for breeding. This study provided a baseline information and identified promising cowpea genetic resources for effective breeding and systematic conservation.